2016
DOI: 10.1155/2016/4396256
|View full text |Cite
|
Sign up to set email alerts
|

Ulcerative Colitis Activity Presenting as Fever of Unknown Origin, in a Patient with Longstanding Disease under Continuous Treatment with Mesalazine

Abstract: Background. The presence of ulcerative colitis (UC) with no bowel symptoms, as fever of unknown origin (FUO), is uncommon. Objective. To describe the case of an 80-year-old woman who presented with fever, with a history of UC under treatment with mesalazine. Case Presentation. She was admitted due to fever lasting for 12 days with no associated symptoms. Seven years earlier, she was diagnosed with UC. After an extended workup for FUO that failed to reach the diagnosis, she underwent a gallium-67 scintigraphy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…IBD, as well as TAK, is a possible cause of FUO 8,9) and it is reported that TAK often complicates IBD. Watanabe et al estimated 6.1% of TAK complicated UC 10) , while Reny et al reported 4 of 44 patients with TAK complicated CD 11) .…”
Section: Case Reportmentioning
confidence: 99%
“…IBD, as well as TAK, is a possible cause of FUO 8,9) and it is reported that TAK often complicates IBD. Watanabe et al estimated 6.1% of TAK complicated UC 10) , while Reny et al reported 4 of 44 patients with TAK complicated CD 11) .…”
Section: Case Reportmentioning
confidence: 99%